Deviant Behavior of SMA PGRI 4 Students in the learning process. - Yanti, Irma; Erianjoni, Erianjoni; Firdaus, Firdaus (Pendidikan Sosiologi, 2014)
This thesis observes the deviant behavior of SMA PGRI 4 students in the learning process. One of the National Education Goal contents based on article 3 of law 2003 National Education System is to develop the studentsâ potential to be faithful and devoted to God Almighty, and to be nice person. But in fact, educational function has not been achieved yet maximally with a number of deviant behavior cases found in SMA PGRI 4 learning process. Based on the matter above, the research problems are formulated as follow: (1) Factors cause students of SMA PGRI 4 have deviant behavior in learning process? (2) The teacherâ efforts in fixing this SMA PGRI 4 Padang studentsâ deviant behavior in learning process?In this study, the researcher uses the theory of differential association by Edwin H. Sutherland, which the environment is very influential to the studentsâ behavior. The approach that is used in this research in qualitative research method, which the approach intends to make a solid theoretical research. While the research type is descriptive to provide a detailed description of the reality under research. The informant retrieval of this research is done by using purposive sampling, informants in this research consisted of 22 people. The collected data type are primary data and secondary data. The data collecting technique is done by observing, intensive interviewing, and document studying. The analysis unit in this research is individual, they are student, teacher, and community member. The data analysis uses Miles and Huberman models, they are data collecting, data reducing, data displaying, and concluding.Â Â Â Â Â Â Â Â Â Â Â Â The result of this study indicates that: (1) The factors cause students have a) the deviant behavior are the classmates influence, b) the teachersâ emotion factor, c) the lack of parentsâ attention, d) the environment influence around the school. (2) The efforts that are done by the teachers to fix the studentsâ deviant behavior are a) giving license card and limiting students out of the classroom, b) giving some pre activities before entering the classroom, c) changing learning method, d) separating students who like to cheat, d) giving motivation and punishment to the students.